Association Genetics of the Cirmamyl Alcohol Dehydrogenase (CAD) and Cirmamate 4-hydroxylase (C4H) Genes with Basic Wood Density in Neolamarckia cadamba - SL, Pang; J, Ismail; BL, Tchin; WS, Ho (Asian Network for Scientific Information, 2012)
Association genetics study is a powerful approach to detect the potential genetic variants (ie, SNPs) underlying the common and complex adaptive traits. Once the quantitative trait nucleotides are identified, such powerful approach provides significant advantages to the forest industry. Hence, attempts were made to discover SNPs from Neolamarclcia cadamba partial C4H (3,538 bp) and CAD (2,354 bp) DNA sequences and further associate those SNPs with basic wood density. Overlapping primers were designed in flanking the partial C4H and CAD DNA frim 12 N.cadamba trees. The amplified DNA fragments were sequenced and the basic wood density measurements were determined for each tree. The sequence variation analyses revealed that there were 60 and 32 SNPs detected in the partial C4H and CAD DNA sequences, respectively. Those SNPs were distributed throughout the exon, intron, 5'-UTR and 3'-UTR regions.